Teacher’s and Students’ Perceptions Between Flipped Classroom and Traditional Classroom At Primary Tamil School - Muniandy, Vimala (School of Social Sciences, USM, 2017)
This research was carried out in order to investigate teacher’s and student’s perceptions to promote active learning through flipped classroom among Tamil school teachers and students. A quantitative research design was used to carry out this study.The dependent variables in this study were teacher’s and student’s perceptions while the independent variables were traditional and flipped classroom. The sample consisted of 20 primary school teachers, 36 students from year 4 from primary Tamil school.Teachers’ perception interview questions were based on Snowden (2012) and a structured questionnaire to determine student perceptions between two different learning environments, flipped classroom and traditional classroom, was adapted from the Student Perception of Instruction Questionnaire (SPIQ) by Johnson and Renner (2012). The researchers distributed the survey questionnaire to primary Tamil school teachers and students. An independent samples t-test was conducted to compare student perception in a traditional and flipped classroom setting. A t-test for independent samples revealed a significant difference in perception between students that learn from a different learning culture (t(57) = -3.71, p < .05). The mean students who learn in a traditional classroom reported significantly different perceptions (M = 4.45, SD = .38) than students who learn in a flipped classroom (M = 4.93, SD = .40). In other words, students in the traditional classroom appear to have a better perception on method of delivery than the flipped classroom. Existing conventional teaching methods need to be transformed to ensure that the country's education system is able to move along the latest and competitive learning. Flipped classroom is one of the methods with potential to realize this vision.